2017
DOI: 10.1038/gim.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Informed decision making and psychosocial outcomes in pregnant and nonpregnant women offered population fragile X carrier screening

Abstract: PurposePopulation-based carrier screening for fragile X syndrome (FXS) is still not universally endorsed by professional organizations due to concerns around genetic counseling for complex information and potential for psychosocial harms.MethodsWe determined uptake levels, decision making, and psychosocial impact in a prospective study of pregnant and nonpregnant Australian women offered FXS carrier screening in clinical settings. Women received pretest genetic counseling, and completed questionnaires when dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…Informed decision-making and patient comprehension (perceived or actual) of results have been studied for various types of genetic testing [1][2][3][4]. For PGx testing, a study of a direct-to-consumer company reported more than 80% understanding of results for response to statin medications without provider support [5].…”
mentioning
confidence: 99%
“…Informed decision-making and patient comprehension (perceived or actual) of results have been studied for various types of genetic testing [1][2][3][4]. For PGx testing, a study of a direct-to-consumer company reported more than 80% understanding of results for response to statin medications without provider support [5].…”
mentioning
confidence: 99%
“…This is particularly pertinent in the era of expanded population-based carrier screening, where hundreds of diseases can be screened simultaneously 26 . In addition to its cost-effectiveness, other factors point towards the expansion of FXS screening criteria 34,35 . In fact, several national population-based screening programs, including FXS carrier screening, have already been implemented and have obtained positive outcomes [25][26][27] .…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%
“…To the Editor: It is encouraging that the article by Metcalfe and colleagues 1 and my corresponding Commentary 2 have stimulated a debate about the timeliness and value of prenatal and preconception screening for fragile X. The subsequent letter by Metcalfe et al 3 reflects the ongoing controversy.…”
Section: Response To Metcalfe Et Almentioning
confidence: 99%